Intergenerational Trauma Narratives: Psychogeographical Analysis of Diasporic Identity in Contemporary Fiction - Parmar, Vastsal (Journal of Research in Vocational Education, 2025)
This paper explores the intricate relationship between identity, migration, and trauma as represented in the poetry of Khal Torabully and Sudesh Mishra. Both poets, hailing from the Indian Ocean diaspora, engage deeply with themes of cultural displacement, historical violence, and the search for belonging. Through an examination of select poems, the study investigates how their work reflects the complex interplay between personal pain and collective identity. By focusing on the poetics of exile, memory, and cultural negotiation, the paper underscores the relevance of their voices in contemporary postcolonial discourse.